Botia (Chromobotia macracanthus Bleeker, 1852) Potential Broodstock Rearing With and Without Shelter - asep permana (Airlangga University, 2020)
Botia fish (clown loach) growth is relatively slow, taking 4-5 months to reach marketable size (2 inch) and 3 years to achieve initial gonad maturation in female and 1 year in male fish. Environmental degradation and overfishing are factors triggering the production of newly potential broodstock. This study aimed to observe the growth response of potential broodstock through rearing technique with and without shelter. Fish were kept inside the aquaria sized 80x40x30 cm with 20 cm water height on the recirculation system. Fish used for shelter treatment were: Total length ± 7.7 cm, height ± 2.09 cm, and weight ± 7.33 g; for no shelter treatment were: Total length ± 6.7 cm, height ± 1.88 cm, and weight ± 4.59 g. Fish were stocked 10 fish / aquarium and fed 3 times / day by at satiation method. Parameters observed were total length, height and weight improvement also water quality. The results showed that growth and feed efficiency had better value when reared with shelter than without shelter. Keyword: Grow-out, Chromobotia macracanthus, shelter